Pengaruh Nilai Belanja Hedonis, Nilai Utilitarian, Suasana Toko Terhadap Pembelian Impulsif Dengan Reaksi Impulsif Sebagai Variabel Intervening (Studi Pada Pengguna Miniso Bandar Lampung) - Agung, Muhammad Fadillah Seftian; Sugeng, Sugeng (Universitas Muhammadiyah Metro, 2023)
Based on field findings, it was found that 64% of consumers had no plans when going toMiniso Kartini Mall Bandar Lampung. Of the 64% of consumers, it is known that 48% ofconsumers make impulse purchases. This shows the phenomenon of impulsive buying thatoccurs at Miniso Kartini Mall Bandar Lampung. So the purpose of this study was todetermine the effect of hedonic shopping values, utilitarian values, and store atmosphere onimpulsive purchases with impulsive reactions as intervening variables in Miniso BandarLampung users. This research is a quantitative research. With this type of explanatory surveyresearch, the sampling technique was accidental sampling, as many as 73 visitors wereencountered during the study. As a measuring tool, 100 questionnaire items were used withLikert scale measurements and analyzed using Path Analysis. The results of the study show that the value of hedonic shopping has a direct effect on impulsive purchases. Utilitarianvalues directly influence impulse buying. Store atmosphere has a direct effect on impulsepurchases. The value of hedonic shopping has a direct effect on impulse purchases.Utilitarian values directly influence impulsive reactions. Store atmosphere has a direct effecton impulsive reactions. Impulsive reactions directly affect impulse purchases. The value ofhedonic shopping directly influences impulsive purchases through impulsive reactions.Utilitarian values have an indirect effect on impulsive purchases through impulsive reactions.Store atmosphere has an indirect effect on impulsive purchases through impulsive reactions.Hedonic shopping values, utilitarian values and store atmosphere together influenceimpulsive purchases through impulsive reactions as intervening variables